A curative effect evaluation of intensity-modulated radiation therapy combined with periorbital triamcinolone acetonide injection in treating thyroid eye disease patients with active extraocular muscle but low CAS - Hao Zhang; Weimin He (Scientific Reports)
Abstract The purpose of this study is to evaluate the effectiveness of intensity-modulated radiation therapy (IMRT) combined with periorbital triamcinolone acetonide injection in treating thyroid eye disease (TED) patients with active extraocular muscle but low CAS. The retrospective observational study was conducted. A total of 156 eligible patients were selected from the TED patient database of the Ophthalmology Department of West China Hospital of Sichuan University. The patient’s relevant medical history was recorded, including gender, age of initial onset, onset eye, the interval between onset and the first visit to our hospital, extraocular muscle condition, smoking status, CAS, NOSPECS, thyroid function, symptoms and signs, and the condition of the affected extraocular muscle. We found that IMRT combined with periorbital triamcinolone acetonide injection has a good therapeutic effect on TED patients with low CAS but significant active extraocular muscles, and there is a significant improvement at 3 months after treatment. Thyroid function and CAS can affect the curative effect of IMRT. Patients with hyperthyroidism had worse effect than those with normal thyroid function. The higher the CAS, the better the effect.